(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The coffee shop industry is growing rapidly, with NextGen Café on Mindanao Avenue, established in 2023, emerging as a leader in sustainability. The café reduces plastic waste by using eco-friendly packaging, offering reusable mugs for dine-in, and utilizing compostable materials for takeout orders. Additionally, NextGen Café emphasizes hygiene through strict cleaning protocols and maintains consistent service quality, ensuring a safe and enjoyable experience for its customers. The study employed a quantitative design to examine the integration of sustainable practices at NextGen Café and their impact on customer perception. A total of 100 respondents participated, comprising 74 customers and 26 employees. Purposive sampling was used to select participants based on criteria relevant to the research objectives. Data collection involved designing the survey, obtaining consent from the establishment, organizing the gathered data, and drawing conclusions for presentation to a review panel. NextGen Café attracts a predominantly younger customer base, mostly aged 19 to 23, highlighting a gap in workforce demographics. While both customers and employees value sustainability, customer engagement is notably higher, indicating a need for improved communication and education among employees. The café’s strong customer loyalty is primarily driven by product quality and variety, with sustainability playing a supportive role. However, the positive correlation between sustainability adoption and customer satisfaction underscores the importance of emphasizing sustainable practices to further strengthen brand loyalty. Sustainable practices enhance customer satisfaction, but maintaining high product quality and service remains vital. Recommendations include improved financial planning, negotiating better supplier terms, introducing age-inclusive and limited-time sustainable offerings, and effectively communicating sustainability efforts. These strategies aim to boost customer satisfaction and market appeal while advancing the café’s sustainability goals.